2014
DOI: 10.3390/electronics3020314
|View full text |Cite
|
Sign up to set email alerts
|

Embroidery and Related Manufacturing Techniques for Wearable Antennas: Challenges and Opportunities

Abstract: This paper will review the evolution of wearable textile antennas over the last couple of decades. Particular emphasis will be given to the process of embroidery. This technique is advantageous for the following reasons: (i) bespoke or mass produced designs can be manufactured using digitized embroidery machines; (ii) glue is not required and (iii) the designs are aesthetic and are integrated into clothing rather than being attached to it. The embroidery technique will be compared to alternative manufacturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(129 citation statements)
references
References 99 publications
2
120
0
Order By: Relevance
“…However, the values of the permittivity are higher compared with garments [8]. This is easily understandable considering that cast acrylic is plastic and denser than woven, knitted etc.…”
Section: Phantom Materials Propertiesmentioning
confidence: 77%
See 2 more Smart Citations
“…However, the values of the permittivity are higher compared with garments [8]. This is easily understandable considering that cast acrylic is plastic and denser than woven, knitted etc.…”
Section: Phantom Materials Propertiesmentioning
confidence: 77%
“…As can be seen from Table II cast acrylic (shell) is a low loss material and this property could characterize it as a good candidate to approximate garments [8], as long as the wearable antennas are generally mounted onto garments. However, the values of the permittivity are higher compared with garments [8].…”
Section: Phantom Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact is due to the availability of the manufacturing technology (industrial embroidery machines), efficient exploitation of the expensive specialized silver threads and repeatability of geometries and layouts [1]. These wearable antennas are suitable for application fields such as health monitoring, physical training, emergency rescue service and law-enforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Later, in 2008, it was found that a better connection and more flexibility can be obtained by making use of a thermally-activated thermal sheet [13], [45] to assemble the different layers. Quite recently, embroidered patch antennas [46] gained in popularity, thanks to the availability of low-cost automatic embroidery machines that operate with conductive yarns, These machines enable the study of different embroidery patterns for antenna and ground plane, which is very useful in the context of RFID tags [47]. Finally, additive techniques may be applied, such as screen or inkjet printing, to define antenna, reflector and ground-plane patterns on the garment [32], [49]- [51].…”
Section: B Materials and Technologiesmentioning
confidence: 99%